Microwave Solid Phase Synthesis, Characterization and Antimicrobial Activities of Mononuclear Cobalt(II) Complex with 4-Chloro-benzoic acid 4-[3-(4-chloro-phenyl)-3-hydroxy-acryloyl]-3-hydroxy-phenyl ester - Xu, Suo-Ping; Li, Tuan-Jie; Xu, Guo; Pei, Yuan (Asian Journal of Chemistry, 2013)
One mononuclear complex has been designed and synthesized by a b-diketone ligand 4-chloro-benzoic acid 4-[3-(4-chloro-phenyl)-3-hydroxy-acryloyl]-3-hydroxy-phenyl ester (L) with CoCl2·6H2O in microwave radiation assistance. The complex was characterized by X-ray crystallography, confirming that the central cobalt(II) was coordinated by four oxygens from two b-diketone ligand and two oxygens from two ethanols. The complex was assayed for in vitro antibacterial (B. subtilis, S. aureus, S. faecalis, P. aeruginosa, E. coli and E. cloacae) activities and showed better antimicrobial activity against Gram positive strains than Gram negative strains.